2017
DOI: 10.1016/j.egja.2017.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic efficacy of ultrasound guided versus landmark-based bilateral superficial cervical plexus block for thyroid surgery

Abstract: a b s t r a c tBackground: The use of bilateral superficial cervical plexus block (BSCPB) to provide analgesia for thyroid operations remains debatable. This study was done to assess the analgesic efficacy and safety of ultrasound (US) guided or landmark-based BSCPB, performed under general anesthesia, compared to systemic narcotics in thyroid surgery. Patients and methods: A total of 69 patients ASA I and II scheduled for thyroid surgery were randomly assigned into three groups (23 patients each): Group (US) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…In this study, all blocks were done by landmark technique by subcutaneous deposition of local anesthetic along the posterior border of sternocleidomastoid. In A recent Egyptian study that compared landmark and ultrasound-guided techniques found no difference in effectiveness and safety [25]. However, another study has concluded that an ultrasound-guided technique had superiority and explained by direct visualization of the nerves, adjacent structures and needle movement that results in faster, denser and longer block [26].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, all blocks were done by landmark technique by subcutaneous deposition of local anesthetic along the posterior border of sternocleidomastoid. In A recent Egyptian study that compared landmark and ultrasound-guided techniques found no difference in effectiveness and safety [25]. However, another study has concluded that an ultrasound-guided technique had superiority and explained by direct visualization of the nerves, adjacent structures and needle movement that results in faster, denser and longer block [26].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, all blocks were done by landmark technique by subcutaneous deposition of local anesthetic along the posterior border of sternocleidomastoid. In A recent Egyptian study that compared landmark and ultrasound-guided techniques found no difference in effectiveness and safety [24]. However, Senapathi et al has concluded that an ultrasound-guided technique had superiority and explained by direct visualization of the nerves, adjacent structures and needle movement that results in faster, denser and longer block [25].…”
Section: Discussionmentioning
confidence: 99%